A Stiffness‐Switchable, Biomimetic Smart Material Enabled by Supramolecular Reconfiguration. Issue 10 (31st January 2022) - Zhao, Dawei; Pang, Bo; Zhu, Ying; Cheng, Wanke; Cao, Kaiyue; Ye, Dongdong; Si, Chuanling; Xu, Guangwen; Chen, Chaoji; Yu, Haipeng
Abstract: In nature, stiffness‐changing behavior is essential for living organisms, which, however, is challenging to achieve in synthetic materials. Here, a stiffness‐changing smart material, through developing interchangeable supramolecular configurations inspired from the dermis of the sea cucumber, which shows extreme, switchable mechanical properties, is reported. In the hydrated state, the material, possessing a stretched, double‐stranded supramolecular network, showcases a soft‐gel behavior with a low stiffness and high pliability. Upon the stimulation of ethanol to transform into the coiled supramolecular configuration, it self‐adjusts to a hard state with nearly 500‐times enhanced stiffness from 0.51 to 243.6 MPa, outstanding load‐bearing capability (over 35 000 times its own weight), and excellent puncture/impact resistance with a specific impact strength of ≈116 kJ m −2 (g cm −3 ) −1 (higher than some metals and alloys such as aluminum, and even comparable to the commercially available protective materials such as D3O and Kevlar). Moreover, this material demonstrates reconfiguration‐dependent self‐healing behavior and designable formability, holding great promise in advanced engineering fields that require both high‐strength durability and good formability. This work may open up a new perspective for the development of self‐regulating materials from supramolecular‐scale configuration regulation. Abstract : A stiffness‐changing biomimetic smart material is developed through a unique water–ethanol solvent‐exchange‐induced supramolecular reconfiguration strategy. The dynamic switchable supramolecular network imparts the material with an interesting self‐regulation behavior in mechanical properties between soft and hard states, self‐healing capability, and excellent formability, which holds great application potential in smart buildings, personal protection devices, soft robots, intelligent devices, and beyond.